A final report in practice-in-industry fish capture - Balagapo, Ismael R. (College of Fisheries, University of the Philippines, 1964)
The Philippines fishery of the Bureau of Fisheries, upon its establishment in the Philippines, attempted among many others to assist in the production of fish in any way legally possible. High priority was given to expansion of fishing effort to new fishing grounds and improvement of the efficiency of our field practice. One phase of our knowledge is to encourage fishermen in the improvement of our new methods and techniques in fishing. Although tropical demersal fishing grounds are not highly productive, the demand for fresh fish in the Philippines, is so great that it is possible to exploit such low producing areas with profit. When the program of the Bureau of Fisheries began to show result in almost all fishing grounds, especially in the immediate vicinity of Manila fishing became profitable. The purpose of this report is to describe the practical training and assay its results, and so far as possible to furnish basis for the research that must be carried out to effect the management of our fishing grounds and conservation of our natural resources.